PENGARUH EMOTIONAL BRANDING TERHADAP LOYALITAS MEREK DENGAN CITRA MEREK SEBAGAI VARIABEL INTERVENING (STUDI PADA RICHEESE FACTORY DI SURABAYA) - FAUJANAH RAFIKA, NIA (Jurnal Ilmu Manajemen (JIM), 2014)
Abstract:Nowdays to win over the market shared, the application of the conventional strategy is not effective because consumers more critical thinking in the choose a product, need a strategy that can provide a certain image in mind of consumers. This study aims analyze and discuss the effect of emotional branding on the brand loyalty with brand image as a intervening variable (study of Richesee Factory in Surabaya). Respondents in this study is Richesee Factory customers who have consumed food at the restaurant Richeese Factory least 2 times. Sample to be taken 220 respondents with accidental sampling technique, questionnaires is spread and analyzed by using the path analysis. The result showed that the emotional branding has a significant effect on brand image, brand image has significant effect on brand loyalty, emotional branding haven’t significant effect to brand loyalty. It maybe Richeese Factory use less media communication in the their marketing. Keywords:emotional branding, brand image, and brand loyalty.